Evaluating the Validity of the Risk Perception Survey for Developing Diabetes Scale in a Safety-Net Clinic Population of English and Spanish Speakers. Issue 1 (February 2020) - Rochefort, Catherine; Baldwin, Austin S.; Tiro, Jasmin; Bowen, Michael E.
Purpose: The purpose of this study is to examine the factor structure of the Risk Perception Survey for Developing Diabetes (RPS-DD) and test for factorial invariance by language (English, Spanish) and gender (males, females) in a clinically engaged, racially diverse, low-education population. Methods: Adult patients seen in a safety-net health system (N = 641) answered an interviewer-administered survey via telephone in their preferred language (English: 42%, Spanish: 58%). Three constructs in the RPS-DD were assessed—personal control (2 items for internal control and 2 for external control), optimistic bias (2 items), and worry (2 items). Single and multigroup confirmatory factor analyses (CFAs) were performed using maximum-likelihood estimation to determine the factor structure and test for invariance. Results: Contrary to previous psychometric analyses in white, educated populations, CFAs supported a 4-factor measurement model with internal and external control items loading onto separate factors. The 4-factor structure was equivalent between males and females. However, the structure varied by language, with the worry subscale items loading more strongly for English than Spanish speakers. Conclusions: The RPS-DD can be used to investigate group differences across gender and language and to help understand if interventions have differential effects for subgroups at high risk for diabetes. Given the increasing prevalence of diabetes among Spanish speakers, researchers should continue to examine the psychometric properties of the RPS-DD, particularly the worry subscale, to improve its validity and clinical utility.